2017
DOI: 10.4236/jwarp.2017.910072
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Level Changes since 1978 in an African City on Basement Rocks: The Case of the CIEH Borehole in Ouagadougou (Burkina Faso)

Abstract: The CIEH piezometer, located in the center of Ouagadougou city presents a water level record spanning the West African Drought which peaked during the 80s and 90s. Its water level is investigated as a potential proxy for groundwater water resources in West African basement rock aquifers submitted to climate changes. 23 boreholes and wells in various land uses and within a 2 km radius around the CIEH piezometer were monitored during the 2013-2014 hydrologic year. The minimum water level occurred in May, at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Burkina Faso is a Sahelian country, with 84% of the population economy and livelihoods based on the agricultural sector. According to a recent study about water resources assessment and management framework (MEE, 2001), agriculture alone accounts for more than 64% of the total water consumer demand. The irrigable areas are estimated at 233,500 ha, and only 14% was effectively explored (Evans et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Burkina Faso is a Sahelian country, with 84% of the population economy and livelihoods based on the agricultural sector. According to a recent study about water resources assessment and management framework (MEE, 2001), agriculture alone accounts for more than 64% of the total water consumer demand. The irrigable areas are estimated at 233,500 ha, and only 14% was effectively explored (Evans et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Most farmers irrigated their crops twice a day, especially in the mornings and afternoons. These practices likely amplified the waste of agricultural water since evaporation was quite high (80% on average) in this region (MEE, 2001). Farmers need adequate technical advisory support on climate smart agricultural practices.…”
Section: Knowledge and Practices Of Farmersmentioning
confidence: 99%
“…We therefore made an initial estimate of hydraulic conductivity values based on the reported transmissivity values and an estimate of the saturated thickness under pumping conditions based on borehole logs, resulting in a range of 0.3-1.7 m day −1 . While Yameogo (2008) reports transmissivity, unconfined storage coefficient, and hydraulic conductivity for a number of sites across the city of Ouagadougou, Mouhouyouddine et al (2017) notes that no successful pumping tests have been undertaken at the observation borehole in Ouagadougou used for long-term monitoring in this research. No pumping test data are available for the remaining three sites (Dingasso, Binde, and Ouda), and no data for unconfined storage coefficients are available for any of the sites.…”
Section: Water Resources Researchmentioning
confidence: 99%
“…Using the same approach as Martin and Thiéry (1987), Filippi et al (1990) developed 1-D reservoir models for six of the sites (Bassinko, Silmissin, Niangoloko, Tibou, Arbinda, and Katchari), but only using <2 years of monitoring data. Mouhouyouddine et al (2017) subsequently also used the same approach to model observed groundwater levels at Ouagadougou from 1978-2015. Recently, Cuthbert, Taylor, et al (2019) used data from this site in a continental scale evaluation of controls on groundwater recharge processes.…”
Section: Study Area and Groundwater Level Observationsmentioning
confidence: 99%
See 1 more Smart Citation